Writing System Variation and Its Consequences for Reading and Dyslexia - Daniels, Peter T.; Share, David L. (Scientific studies of reading, 2018)
Most current theories of reading and dyslexia derive from a relatively narrow empirical base: research on English and a handful of other European alphabets. Furthermore, the two dominant theoretical frameworks for describing cross-script diversity-orthographic depth and psycholinguistic grain size theory-are also deeply entrenched in Anglophone and Eurocentric/alphabetocentric perspectives, giving little consideration to non-European writing systems and promoting a one-dimensional view of script variation, namely, spelling-sound consistency. Most dyslexics struggle to read in languages that are not European and orthographies that are not alphabetic such as abjads, abugidas, or morphosyllabaries; hence the full spectrum of the world's writing systems needs to be considered. The global picture reveals multiple dimensions of complexity. We enumerate 10 such dimensions: linguistic distance, nonlinearity, visual complexity, historical change, spelling constancy despite morphophonemic alternation, omission of phonological elements, allography, dual purpose letters, ligaturing, and inventory size. We then consider how these 10 dimensions might affect variation in reading ability and dyslexia.